First record of Chestnut-fronted Helmet-Shrike at Chilo Gorge Lodge, Zimbabwe - Grobbelaar, Lizet (Biodiversity Observations, 2014)
[in] a patch of sand forest where we recorded a small flock of Chestnut-fronted Helmet-Shrikes ...